Pengaruh Indeks Pembangunan Manusia, Upah Minimum Regional, dan Tingkat Partisipasi Angkatan Kerja terhadap Kemiskinan di Sumatera Utara Tahun 2001-2023 - Septian, Yan; Suharianto, Joko (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study analyzes the human development index, regional minimum wage, and labor force participation rate on poverty in North Sumatra in 2001-2023. The data used is secondary data in the form of time series obtained from the publication of the Central Bureau of Statistics. The analysis method used is multiple regression with E-Views software. The results showed that the human development index has no effect, the regional minimum wage has a negative effect and the labor force participation rate has a negative and significant effect on poverty, which indicates that an increase in the human development index tends to not affect poverty because it has a positive value. In contrast, the regional minimum wage and labor force participation rate show a negative and significant effect on poverty. Simultaneously, the human development index, regional minimum wage and labor force participation rate have a significant effect on poverty.